Environmental enrichment condition does not alter glutamine synthetase activity in the hippocampus and cerebral cortex of Swiss albino mice. Issue 1 (2015) - Viola, Giordano G.; Binder, Luisa B.; , Eduarda Muccini; Martins, Wagner C.; Cristaldo, Paulo F.; Tasca, Carla I.
No abstract available